2018
DOI: 10.1007/s00737-018-0901-7
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the prevention of postpartum depression in adolescent mothers: a systematic review

Abstract: Postpartum depression (PPD) is a major public health problem affecting 10-57% of adolescent mothers which can affect not only adolescent mothers but also their infants. Thus, there is a need for interventions to prevent PPD in adolescent mothers. However, recent systematic reviews have been focused on effective interventions to prevent PPD in adult mothers. These interventions may not necessarily be applicable for adolescent mothers. Therefore, the purpose of this review was to examine the effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
2
38
0
4
Order By: Relevance
“…These results can be compared with the ndings of previous reviews. Sangsawang et al [21] found effective results for psychological and psychosocial interventions, whereas Werner et al [19] found both signi cant and non-signi cant effects for psychological and psychosocial interventions. In line with those ndings, we found psychological and psychosocial interventions to be effective in the prevention of PPD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results can be compared with the ndings of previous reviews. Sangsawang et al [21] found effective results for psychological and psychosocial interventions, whereas Werner et al [19] found both signi cant and non-signi cant effects for psychological and psychosocial interventions. In line with those ndings, we found psychological and psychosocial interventions to be effective in the prevention of PPD.…”
Section: Discussionmentioning
confidence: 99%
“…PPD is one of the most frequent mental diseases of the perinatal period [1] and the importance of prevention of PPD has been highlighted frequently [11,19,21]. Therefore, the aim of this current review was to provide an overview of current literature on preventive interventions for PPD in adult mothers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Centering Teen Pregnancy Program (CTP program) used in this study was guided by the Nursing Practice Guideline for Teenage Pregnancy 23 and the findings from previous studies. 24 The original guideline was developed using an evidence-based approach. The components of the original guideline included a modification of attitude towards pregnancy and an allocation of family and peer support using the centering program.…”
Section: Introductionmentioning
confidence: 99%